NEDD9 expression is correlated with epithelial-to-mesenchymal transition markers in colorectal cancer - Xue, Yu-Zheng (Int J Clin Exp Pathol, 2017)
The epithelial-to-mesenchymal transition (EMT) is a critical step in tumor metastasis. NEDD9 has been shown to be an oncogene in colorectal cancer. However, little is known about the relationship between NEDD9 and EMT in colorectal cancer metastasis. A total of 63 pairs of freshly frozen colorectal cancer tissues and adjacent noncancerous tissues were evaluated for NEDD9 gene expression using quantitative real-time PCR. The expression of NEDD9 and three epithelial-mesenchymal transition (EMT)-related proteins (E-cadherin, β-catenin and vimentin) was examined in 122 colorectal cancers by immunohistochemistry. The expression of NEDD9 was markedly increased in colorectal cancer tissues compared with adjacent noncancerous tissues. The expression level of NEDD9 was positively correlated and TNM stage but not with other clinicopathological features of colorectal tumors. Furthermore, the expression of NEDD9 was strongly associated with the loss of epithelial marker E-cadherin and acquired expression of the mesenchymal markers nuclear β-catenin and vimentin. These findings suggested that NEDD9 might promote EMT and the progression of colorectal cancer, and thus may be a potential therapeutic target of colorectal cancers.